2008
DOI: 10.1099/mic.0.2008/017228-0
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial involvement in aspirin-induced apoptosis in yeast

Abstract: We have previously reported that aspirin induces apoptosis in manganese superoxide dismutase (MnSOD)-deficient Saccharomyces cerevisiae cells when cultivated on the non-fermentable carbon source ethanol. Here, we investigated the role of mitochondria in aspirin-induced apoptosis. We report that aspirin had an inhibitory effect on cellular respiration, and caused the release of most of the mitochondrial cytochrome c and a dramatic drop in the mitochondrial membrane potential (DY m ). Also, aspirin reduced the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…These results indicate a clear link between mitochondrial respiration, ROS formation and diclofenac toxicity. Interestingly, another NSAID, aspirin, has also been linked to mitochondrial dysfunction in yeast, leading to apoptosis (Sapienza et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate a clear link between mitochondrial respiration, ROS formation and diclofenac toxicity. Interestingly, another NSAID, aspirin, has also been linked to mitochondrial dysfunction in yeast, leading to apoptosis (Sapienza et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicate that cytochrome c release is a critical mediatory mechanism of apoptotic cell death induced by NSAIDs [39]. In fact, it has also been shown that aspirin-induced apoptosis of S. cerevisiae cells deficient in manganese superoxide dismutase (MnSOD) and cultivated in nonfermentable ethanol medium is preceded by the early release of cytochrome c , followed by a drastic fall in ΔΨ m [93]. …”
Section: Cox-independent Nsaid-induced Apoptotic Cell Deathmentioning
confidence: 99%
“…Likewise, it has been shown that the mitochondria of S. cerevisiae cells constitute a critical target of NSAIDs such as aspirin [32], the proapoptotic effects of which were shown to be associated with inhibition of the electron transport chain [93]. Similarly, Van Leeuwen and coworkers [33] observed that growth inhibition and apoptosis of S. cerevisiae cells caused by treatment with the NSAID diclofenac were due to mitochondrial dysfunctional events involving the inhibition of the electron transport chain.…”
Section: Cox-independent Nsaid-induced Apoptotic Cell Deathmentioning
confidence: 99%
“…SA inhibited the activities of NADH dehydrogenase and succinate dehydrogenase in H. armigera. Aspirin, a derivative of SA, has been reported as a uncoupler of oxidative phosphorylation in Yeast (Sapienza et al 2008), and inhibitor of electron transport chain at complex I and complex II in rat liver mitochondria (Somsundaram et al 1997). According to Battaglia et al (2005), the most probable site for binding the SA is Fe 3+ of Fe-S clusters of mitochondrial complexes.…”
Section: Discussionmentioning
confidence: 99%